Anti-Inflammatory, Antinociceptive and Antipyretic Effects of Extracts from Snakehead Fish (Channa Striatus and C. Lucius). - Mohd Johari, Azlina (2008)
Channa spp. is a snakehead fish and widely consumed in Malaysia. A study was conducted to determine the effect of Channa striatus and Channa lucius extracts on carrageenan-induced synovitis in rabbits. The antinociceptive and antipyretic properties of both Channa spp. were also investigated in mice. The extracts of C. striatus and C. lucius were prepared as water and aqueous portion of chloroform: methanol extracts, respectively. Sixteen rabbits were randomly assigned into four groups. Each group of rabbits was treated orally 30 minutes before the induction of inflammation with C. striatus (60 mg/kg), C. lucius (60 mg/kg), ketoprofen (3 mg/kg) and saline solution (control), respectively. The right stifle joint was intra-articularly injected with 0.5 mL of 1% carrageenan. Whole blood was taken for serum thromboxane (TxB2) assay before and at 1, 3, 6, 9, 12 and 24 hour (h) after the induction of inflammation. Synovial fluid and synovial membrane were collected during post-mortem for analysis and histopathology. The results indicated that TxB2 synthesis was significantly (p<0.05) inhibited for 12 h after oral dosing of ketoprofen in rabbits. Serum TxB2 for C. striatus was lower than that of the control group at 1, 3, 6 and 12 h. As for C. lucius, TxB2 synthesis was inhibited at 9 and 12 h. However, the inhibition of TxB2 for both Channa spp. was small and not significant as compared to the control group. As for C. striatus and ketoprofen treated groups, the total white blood cell (WBC) count was reduced compared to the control group but was not significant different. Histopathological results indicated a mild infiltration of leucocytes in the synovial membrane of ketoprofen treated rabbits. However in the control, C. striatus and C. lucius treated groups showed massive leucocyte infiltration, congestion in the blood vessels and fibrin exudation. As for the analgesic activity of Channa spp., twenty four mice were allocated equally into three treatment groups and one control group. The extracts of C. striatus (60 mg/kg), C. lucius (60 mg/kg) or ketoprofen (1 mg/kg) was administered intraperitoneally, 30 minutes before injection of acetic acid. Both extracts of the local Channa spp. and ketoprofen showed significant (p<0.05) reductions in the number of abdominal constriction and hind limb stretching as compared to the control group. As for the antipyretic effect of the Channa spp. extracts, twenty four mice were equally divided into three treatment groups and one control group. Mice were injected with 30% (w/v) suspension of yeast in saline at the dosage of 10 mL/kg subcutaneously. The temperature was recorded 18 hour before and measured every half an hour for 5 hours after dosing. C. striatus (60 mg/kg) and C. lucius (60 mg/kg) reduced hyperthermia significantly (p<0.05) at 2.5 to 5 h and 3 to 4 h, respectively. Ketoprofen (1 mg/kg) caused significant inhibition (p<0.05) at 0.5, 1, 1.5, 2, 3 and 3.5 h after dosing. In summary, C. striatus and C. lucius extracts may possess antinociceptive and antipyretic in mice but at 60 mg/kg, both fish extracts did not produce anti-inflammatory activity in rabbits.